2007
DOI: 10.1016/j.neuroscience.2006.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Ketones inhibit mitochondrial production of reactive oxygen species production following glutamate excitotoxicity by increasing NADH oxidation

Abstract: Dietary protocols that increase serum levels of ketones, such as calorie restriction and the ketogenic diet, offer robust protection against a multitude of acute and chronic neurological diseases. The underlying mechanisms, however, remain unclear. Previous studies have suggested that the ketogenic diet may reduce free radical levels in the brain. Thus, one possibility is that ketones may mediate neuroprotection through antioxidant activity. In the present study, we examined the effects of the ketones β-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
313
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(346 citation statements)
references
References 56 publications
12
313
5
1
Order By: Relevance
“…6,10 An antioxidant action of KB can result from the increase in NADH oxidation and/or the improvement of mitochondrial function. 10,16 In addition, in a previous study we reported in a free cell system that both isomers of BHB can scavenge the hydroxyl radical with an IC50 of 2 to 3 mmol/L. 10 We also showed that both isomers reduce the number of Et-positive hippocampal cells during glycolysis inhibition, suggesting that they retain their capacity to scavenge ROS in a cellular system.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…6,10 An antioxidant action of KB can result from the increase in NADH oxidation and/or the improvement of mitochondrial function. 10,16 In addition, in a previous study we reported in a free cell system that both isomers of BHB can scavenge the hydroxyl radical with an IC50 of 2 to 3 mmol/L. 10 We also showed that both isomers reduce the number of Et-positive hippocampal cells during glycolysis inhibition, suggesting that they retain their capacity to scavenge ROS in a cellular system.…”
Section: Discussionmentioning
confidence: 66%
“…[6][7][8][33][34][35][36] The improvement of mitochondrial function and ATP production has been suggested by several studies as the main mechanism involved in the neuroprotective action of KB. 11,16,17,33 We also tested the protective effect of pyruvate and lactate, which can also be used by brain as alternative substrates to glucose through its metabolism by the tricarboxylic acid cycle. In agreement with previous studies, [37][38][39] we observed a reduction of neuronal death in the in vitro model by both substrates, while the effect of pyruvate was similar to that of D-BHB, lactate was less effective.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS are capable of inducing damage and, in severe cases, cell death through mitochondrial alterations leading to the release of cytochrome c [42,43] through activation of the JNK pathway [44] or by activation of nuclear factor-κB (NF-κB) transcription factors [45] . The ability to control ROS is thus critical in neurodegenerative diseases, because neuronal damage occurs when the ''oxidant-antioxidant'' balance is disturbed in favor of excess oxidative stress [46] . A recent study suggests that a ROS-scavenger effectively protected human neuroglioma against both necrotic and apoptotic cell death induced by hydrogen peroxide [47] .…”
Section: Excitotoxicity and Oxidative Stressmentioning
confidence: 99%
“…In neocortical neuron slices, the ketone bodies β-hydroxybutyrate and acetoacetate prevent cell injury induced by the oxidative stressors hydrogen peroxide and the thiol oxidant diamide [13]. These ketone bodies also inhibit glutamate-induced mitochondrial reactive oxygen species generation [14]. Oxidative stressors may contribute to the development of epilepsy (reviewed in [15]).…”
Section: Do Ketone Bodies Mediate the Effects Of The Ketogenic Diet?mentioning
confidence: 99%